A serine protease extracted from Trichosanthes kirilowii induces apoptosis via the PI3K/AKT-mediated mitochondrial pathway in human colorectal adenocarcinoma cells. Issue 2 (17th December 2015) - Song, Li; Chang, Jiao; Li, Zhuoyu
Abstract : A novel protein TKP extracted from T. kirilowii fruit exerted potential anti-colorectal cancer activity by inducing apoptosis, which was regulated by the PI3K/AKT-mediated mitochondria-dependent pathway. Abstract : Trichosanthes kirilowii exhibits various biological functions including anti-inflammatory, antidiabetic and anticancer activities. In this study, a novel protein with anti-cancer activity, named as TKP, was purified from Trichosanthes kirilowii fruit by cell-base screening. Mass spectrometry and protease assays revealed that TKP is a serine protease. TKP decreased cell viability in a concentration-and time-dependent manner in human colorectal adenocarcinoma cells. Notably, TKP presented very little effect on human colon epithelial cell line NCM460. Furthermore, TKP inhibited colorectal adenocarcinoma cells to aggregate into viable colony clusters and induced cell apoptosis. The loss of mitochondrial membrane potential, upregulation of cytochrome c and Bax, downregulation of Bcl-2, and activation of caspase-9 and -3 were observed, indicating mitochondria-dependent apoptosis induced by TKP. We found that TKP activated MAPK/ERK and suppressed PI3K/AKT signaling. Inhibition of MAPK/ERK signaling by employing inhibitor PD98059 did not antagonize the effects of TKP. Treatment with PI3K inhibitor LY294003 increased the impact of TKP on mitochondria-related apoptosis proteins (cytochrome c, Bcl-2, Bax, caspase-9 and caspase-3) and cell apoptosis. On the contrary, PI3K/AKT activator insulin-like growth factor-1 reversed the effects of TKP. Taken together, our results demonstrated that TKP has potential anti-colorectal cancer activity by inducing apoptosis, which was regulated by the PI3K/AKT-mediated mitochondria-dependent pathway.